FORMULASI SEDIAAN ODOL KOMBUCHA BUNGA TELANG SEBAGAI PRODUK BIOTEKNOLOGI FARMASI DAN ANTIMIKROBA (Staphylococcus aureus, Streptococcus mutan, Candida albicans).Telang flower kombucha has been widely studied as a probiotic drink that can boost the immune s - Firman Rezaldi; Yuliana Kolo; Ratna Fitry Yenny; Vevi Maritha; Novi Ayuwardani; Andri Tri Cahyono; Fitria Eka Resti Wijayanti; Rifkarosita Putri Ginaris; Reni Purbanova (PHARMACIA, 2024)
Telang flower kombucha has been widely studied as a probiotic drink that can boost the immune system which in recent research has various pharmacological activities as a source of antimicrobials, especially in health problems related to dental disease. Previous studies and this is still a renewable research has found that mouthwash formulations and preparations made from an active ingredient of seagrass kombucha fermented solution have been shown to be able to inhibit the growth of Staphylococcus aureus, Candida albicans, and Streptococcus mutans. This study aims to make toothpaste formulations and preparations with an active ingredient of telang flower kombucha fermented solution as a pharmaceutical biotechnology product designed to inhibit the growth of Staphylococcus aureus and mutant Streptococcus bacteria as well as pathogenic fungi in the form of Candida albicans species. This type of research is a laboratory experiment in which we make a toothpaste base without the active substance as a negative control. Provide toothpaste that is sold in the market as a positive control. Make formulations and preparations of toothpaste with active ingredients from the fermented butterfly pea flower kombucha solution which includes concentrations of 20%, 30% and 40%. Data analysis was used through one way ANOVA where in the results of the study each preparation had a P value <0.05, so that further tests could be carried out through post hoc analysis. eggplant at a concentration of 40% was significantly different from 20% and 30% as a pharmaceutical biotechnology product in inhibiting the growth of the three test microbes and the results of this study it can be concluded that the formulation and preparation of toothpaste made from the active ingredient of butterfly pea flower kombucha fermentation solution is the best treatment as an antimicrobial and pharmaceutical biotechnology products.